A novel Fe–N–C catalyst for efficient oxygen reduction reaction based on polydopamine nanotubes. Issue 44 (2nd November 2017) - Tang, Feng; Lei, Haitao; Wang, Shujun; Wang, Huixin; Jin, Zhaoxia
Abstract : An efficient 1D Fe–N–C electrocatalyst for the oxygen reduction reaction (ORR) derived from porous polydopamine nanotubes has been fabricated. Abstract : One-dimensional Fe–N-codoped porous carbon materials have shown great potential as sustainable and efficient oxygen reduction reaction (ORR) catalysts. Herein, a highly active ORR 1D Fe–N–C catalyst has been developed by pyrolyzing a complex of polydopamine nanotubes and Fe(NO3 )3 at 800 °C. Porous PDA nanotubes as a resource for nitrogen-doped carbon and a coordination platform for Fe 3+ can provide well-distributed catalytic sites (Fe–N) after pyrolysis, and generate graphene-like carbon covers with proper thicknesses on Fe/Fe3 C nanoparticles that effectively prevent agglomeration. Thanks to the 1D mesoporous morphology and hybrid composition, the rationally designed catalyst exhibits comparable ORR activity to the commercial Pt/C catalyst, and superior durability and methanol tolerance in alkaline media. Polydopamine nanotubes have demonstrated effects in the fabrication of efficient ORR catalysts which can be described as "killing three birds with one stone". The excellent electrocatalytic performance makes this novel 1D Fe–N–C catalyst a promising non-precious metal catalyst for practical fuel cell application.